Analysis of K-Pop Idol Brand Ambassador ad Content on Instagram Social Media - Stevania Randalia (Jurnal Impresi Indonesia, 2025)
Advertising campaigns with Korean celebrities as brand ambassadors is a prominent strategy utilised by Indonesian e-commerce brands. However, previous researches showed inconsistencies of the effectiveness of these type of campaigns attributed to two underlying factors: incompatibility of the said brand ambassadors with the product and audience demographics; or when content itself fails to capture audience engagement. This research focuses on the latter by analyzing formats and topics found in @bliblidotcom Instagram contents with idol NCT 127 as their brand ambassadors, considered to be successful in raising brand awareness and generating high engagement. A quantitative content analysis was conducted on 73 contents with NCT 127 and compared the formats and typologies used in each content with the engagement obtained. This research’s findings reaffirm previous studies, where brand ambassadors can increase audience engagement in the form of likes regardless of the message formats and topics. However, for engagement in the form of comments, the message format should optimize the visual strength of the brand ambassadors in combination with topics that encourage direct (live events) and indirect/parasocial (incentives and interactive related to the brand ambassador) interactions between the audience and Korean celebrities.